Dancers' Perceived and Actual Knowledge of Anatomy. Issue 2 (June 2017) - Kotier, Dana H.; Lynch, Meaghan; Cushman, Daniel; Hu, Jason; Garner, Jocelyn
Dancers are highly susceptible to musculoskeletal injuries and frequently require interaction with medical professionals. While many dancers have a finely tuned awareness of their bodies, their knowledge of the fundamentals of human anatomy is not uniform. There is a paucity of literature on the benefits of human anatomy education in dancers, though it seems intuitive that there should be a relationship. The purpose of this study was to assess dancers' perceived and actual knowledge of basic musculoskeletal anatomy and its relationship to function. Adult dancers at the undergraduate, pre-professional, and professional levels were surveyed through an anonymous online questionnaire. Questions included demographic information, dance techniques studied, anatomy training, and injury history. Subjects rated their perceived knowledge of anatomy and were tested with 15 multiple-choice questions on basic musculoskeletal anatomy. Four hundred seventy-five surveys were completed. Ordinal regression showed a correlation of perceived to actual knowledge of anatomy (p < 0.001). Factors that correlated with increases in both perceived and actual knowledge of anatomy included having taken an anatomy course of any type (p < 0.001) and increased age (p ≤ 0.001). Years of dance training and professional dancer status both significantly correlated with increased knowledge of anatomy (p < 0.001) but not perceived knowledge. Chi-square analysis showed that dancers with training in either modern or jazz dance had a significantly higher perceived, but not actual, knowledge when compared to those without training in those styles of dance (p < 0.001 and p = 0.011, respectively). In conclusion, dancers generally scored well on questions pertaining to basic musculoskeletal anatomy, and their perception correlated with their actual knowledge of anatomy. Factors that contribute to dancers' knowledge of anatomy include age, years of experience, professional dancer status, and anatomy training.